A coopetition-driven strategy of parallel/perpendicular aromatic stacking enabling metastable supramolecular polymerization - Zhao Gao; Xuxu Xie; Juan Zhang; Wei Yuan; Hongxia Yan; Wei Tian (Nature Communications)
Abstract Metastable supramolecular polymerization under kinetic control has recently been recognized as a closer way to biosystem than thermodynamic process. While impressive works on metastable supramolecular systems have been reported, the library of available non-covalent driving modes is still small and a simple yet versatile solution is highly desirable to design for easily regulating the energy landscapes of metastable aggregation. Herein, we propose a coopetition-driven metastability strategy for parallel/perpendicular aromatic stacking to construct metastable supramolecular polymers derived from a class of simple monomers consisting of lateral indoles and aromatic core. By subtly increasing the stacking strength of aromatic cores from phenyl to anthryl, the parallel face-to-face stacked aggregates are competitively formed as metastable products, which spontaneously transform into thermodynamically favorable species through the cooperativity of perpendicular edge-to-face stacking and parallel offset stacking. The slow kinetic-to-thermodynamic transformation could be accelerated by adding seeds for realizing the desired living supramolecular polymerization. Besides, this transformation of parallel/perpendicular aromatic stacking accompanied by time-dependent emission change from red to yellow is employed to dynamic cell imaging, largely avoiding the background interferences. The coopetition relationship of different aromatic stacking for metastable supramolecular systems is expected to serve as an effective strategy towards pathway-controlled functional materials.